Dance and early childhood education: methodological proposal for a decolonial education (Revista NUPEART, 2023)
Early Childhood Education has changed its approach and implementation in recent decades. The childcare concept is gone. It has also been abandoned the idea of it being a prior step to Basic Education, integrating the formal basic curriculum. However, we need to discuss the official documents and the theoretical references, mostly European, as well as to discuss the possibility of implementing them in a decolonial perspective. Therefore, this article intends to analyze the National Common Curricular Base (BNCC) with regard to Early Childhood Education and the National Curriculum Guidelines for Early Childhood Education (RCNEI), as well as the proposed curriculum for the same age group in Europe, more specifically in Italy. Then we will discuss a proposal for the implementation of the BNCC in a decolonial perspective. Although teaching of the Arts is not anticipated in this age group, we recommend that the research be methodologically conducted by artistic means. Therefore, we will bring the experience of the “Kangaroo Project – dancing at school” as a possibility of dialogue between the objectives foreseen in the BNCC and its implementation in another epistemological basis. Learning that starts from personal and bodily research, with the creation of authorial resolutions and, at the same time, in interaction with others and the environment, breaking the current logic of the instituted teaching-learning process.
Keywords: dance; early childhood education; decolonial education; methodology; Kangaroo Project